The prison officer: the inside story of life behind bars - Glaister, Gen (Penguin Books, 2024)
Becoming a prison officer was Gen's burning ambition despite her background making this an unlikely career choice. At twenty-three, full of hopes and dreams of helping those that needed it most within the prison system, she discovered the reality of life behind bars that no training could possibly have prepared her for. In this searing account of her years as a prison officer, Gen shares how she learned to use her heart, her humour and sheer bloody-mindedness to make a difference to the men who lived by a different set of rules, finding her place amongst gangsters, killers and traffickers